2017
DOI: 10.1177/1747493017743059
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after young stroke: A systematic review

Abstract: Background The incidence of stroke in young adults is increasing. While many young survivors are able to achieve a good physical recovery, subtle dysfunction in other domains, such as cognition, often persists, and could affect return to work. However, reported estimates of return to work and factors affecting vocational outcome post-stroke vary greatly. Aims The aims of this systematic review were to determine the frequency of return to work at different time points after stroke and identify predictors of ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
131
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 48 publications
11
131
1
2
Order By: Relevance
“…Most patients with stroke survive the acute episode and live with enduring disability. Upper limb paresis in particular is one of the most common long‐term disabilities after stroke and constitutes one, if not the most limiting factor in the reintegration to daily life and return to work . Effective therapies to improve motor function after stroke are yet to be developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with stroke survive the acute episode and live with enduring disability. Upper limb paresis in particular is one of the most common long‐term disabilities after stroke and constitutes one, if not the most limiting factor in the reintegration to daily life and return to work . Effective therapies to improve motor function after stroke are yet to be developed.…”
mentioning
confidence: 99%
“…Upper limb paresis in particular is one of the most common long-term disabilities after stroke 1 and constitutes one, if not the most limiting factor in the reintegration to daily life 2 and return to work. 3,4 Effective therapies to improve motor function after stroke are yet to be developed. Therapies targeting restorative processes encompass brain stimulation techniques.…”
mentioning
confidence: 99%
“…5,10,27,28 However, men and women were functionally independent at discharge RTW in a similar pattern. 5,10,27,28 However, men and women were functionally independent at discharge RTW in a similar pattern.…”
Section: Discussionmentioning
confidence: 90%
“…10,11 Further, the RTW varied depending on occupational groups. This finding is in line with previous literature reviews based on self-reported RTW.…”
Section: Discussionmentioning
confidence: 99%
“…Edwards, Kapoor, Linkewich and Swartz () aimed to investigate who was most likely to return to work after stroke, and what factors were associated with this outcome. Although the authors nominated the review's cohort as “young stroke”, the criteria included adult survivors of working aged between 18 and 64 years, consistent with the Global Burden of Disease (Krishnamurthi et al ., ), and a mean, between‐study age ranging from 37 to 55 years.…”
Section: Commentarymentioning
confidence: 99%